Decreasing hazards of Alzheimer's disease with the use of antidepressants: mitigating the risk of depression and apolipoprotein E. (31st May 2017) - Burke, Shanna L.; Maramaldi, Peter; Cadet, Tamara; Kukull, Walter
Abstract : Objective: Alzheimer's disease (AD) is a neurodegenerative disease, manifesting in clinically observable deficits in memory, thinking, and behavior that disproportionately affects older adults. Susceptibility genes, such as apolipoprotein ε4, have long been associated with an increased risk of AD diagnosis. Studies have shown associations between depression and increased risk of AD development. Furthermore, findings from previous investigations suggest mixed effects in the use of psychotropic medication in older adults. The hypothesis for this study is that antidepressant use modifies the increased hazard of depression or such that a non‐significant hazard will result with respect to eventual AD development. Methods: Utilizing data from the National Alzheimer's Coordinating Center, we examined evaluations of 11, 443 cognitively intact participants. Survival analysis was used to explore relationships between depression, apolipoprotein E, AD diagnosis, and antidepressant use. Results: An analytical sample of 8732 participants with normal cognition was examined. Among users of antidepressant medication, the hazard, in most cases, was no longer statistically significant. One generic medication showed protective benefits for users ( p <  0.001). In addition, there was a statistically significant relationship between recent depression ( n  = 2083; p <  0.001), lifetime depression ( n  = 2068; p <  0.05), and ε4 carrier status ( n  = 2470; p <  0.001) and AD development. Conclusions: The findings suggest that a mechanism related to antidepressant use may reduce the hazard of eventual AD. Furthermore, the findings reinforce the association between depression, apolipoprotein E (APOE) ε4, and AD diagnosis. This study contributes to the emerging literature exploring interventions aimed at decreasing the risk of AD by targeting potentially modifiable psychosocial risk factors such as depression. Copyright © 2017 John Wiley & Sons, Ltd.